𝒬K Spaces of Several Real Variables. (13th May 2014) - Bao, Guanlong; Wulan, Hasi
Abstract : We introduce a new space, 𝒬 K ( ℝ n ) space, of several real variables with nondecreasing functions K . By giving basic properties of the weighted function K, by establishing a Stegenga-type estimate, and by introducing the K -Carleson measure on ℝ + n + 1, we obtain various characterizations of 𝒬 K ( ℝ n ) space.